Efeito de altas pressões no composto intermetálico Bi3Ni nanoestruturado produzido por Mecano-Síntese - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This thesis describes results of the investigation of the Bi3Ni crystalline structure using Xray diffraction (XRD) measurements recorded in a synchrotron source under extreme conditions (high pressures). The Bi3Ni compound in powder form The polycrystalline powder sample was synthesized by the mechano-synthesis method using a planetary mill. Then it was characterized under ambient conditions by X-ray diffraction in reflection geometry, Rietveld refinement, scanning and transmission electron microscopy, Raman spectroscopy and magnetic measurements. Afterwards, a sample was compacted in an anvil cell, and XRD data in situ were collected using monochromatic radiation with energy of 20 KeV. Diffractograms show the presence of the Bi3Ni phase up to 30 GPa and using the Rietveld method. The diffractograms were refined and the values of the network parameters as a function of pressure were used in the 3rd order Birch-Murnargan equation (EoS-BM) to obtain the values of the volumetric module (B0) and its first derivative ( B'0) and the values of the linear modules B0a, B'0a, B'0b, B'0b, B0c and B'0c. During the Rietveld refinement, the Stephens model was used to build anisiotropic microdeformation maps as a function of pressure to analyze the direction of greatest deformation. Using atomic coordinates and refined network parameters and those obtained from ab initio calculations, layer structures with a radius of 30 Å were built to study functions of pair distributions and Fourier maps to investigate charge density as a function of pressure. Short-range chemical order (CSRO) were also built.
Keywords: Raios X - Difração; Nanopartículas; Termodinâmica; Método de Rietveld; Síntese mecânica; CIÊNCIAS EXATAS E DA TERRA: FÍSICA: FÍSICA DA MATÉRIA CONDENSADA; Refinamento Rietveld; Módulo de Bulk; Função de distribuição de pares